Seroprevalence and Potential Risk Factors of Toxocariasis among General Population in Southwest Iran: Implications on the One Health Approach - Masoud Foroutan; Aida Vafae Eslahi; Shahrzad Soltani; Naser Kamyari; Ehsan Moradi-Joo; Jean-Francois Magnaval; Milad Badri (Journal of Immunology Research)
Toxocariasis is one of the most common zoonotic diseases distributed worldwide. This study aimed to estimate the seroprevalence of anti-Toxocara immunoglobulin G (IgG) antibodies and the associated risk factors among general populations living in urban and rural areas of Abadan and Khorramshahr cities in Khuzestan Province, Southwest Iran. This cross-sectional study was conducted between March and September 2022. There were 363 participants (190 females and 173 males) aged from <20 to ≥60 years old. Anti-Toxocara IgG antibodies in serum samples were measured using a commercially available enzyme-linked immunosorbent assay (ELISA). A structured questionnaire was employed to collect information regarding sociodemographic status and probable risk factors associated with toxocariasis. It was found that the seroprevalence rate in males (15.0%, 95% CI = 10.47–21.11) was higher than in females (10.5%, 95% CI = 6.92–15.70). Moreover, we observed that the seroprevalence was higher in participants at younger ages compared to other age ranges (COR = 2.55, 95% CI = 0.92–7.12, p =0.073). The findings of the univariate analysis revealed that residency in rural areas (p <0.001), using unpurified water (p <0.001), contact with dog (p =0.002), contact with soil (p <0.001), consumption of improperly washed vegetables (p <0.001), and history of drinking untreated water (p <0.001) were risk factors associated with toxocariasis. Further comprehensive studies with a focus on humans and animals should be designed in different areas of the Province. The data represented by the current study are useful to health policymakers to consider precise surveillance and effective prevention measures to control this zoonotic infection among general populations.